THE IMPACT OF BUDGET INTEGRATION IN THE GOVERNMENTAL ACCOUNTING SYSTEM ON ACHIEVING FINANCIAL SUSTAINABILITY - Lina Khalid jaafer Ibrahim; Houda Ben Mabrouk (Scholar Express Journals, 2025)
The goal of the study is to determine how the government accounting system functions as a mediator in the link between budget integration and enhancing financial sustainability in the Iraqi Ministry of Higher Education. This is accomplished by developing a theoretical framework for the primary and secondary variables of the current study. Then, the variables are evaluated in the Iraqi Ministry of Higher Education by examining how integrating budgets with the aforementioned dimensions improves financial sustainability in the ministry while elucidating the role of the government accounting system as a mediator. By creating a questionnaire and distributing it to a sample of 150 financial professionals at the Iraqi Ministry of Higher Education using a thorough inventory procedure, the researcher relied on the descriptive analytical approach. Data was gathered and analyzed using the SPSS software. The investigation came to the following key conclusions: Given the existence of a practical system for government courts in the Iraqi Ministry of Higher Education, as well as the existence of a statistically significant contribution and governmental contribution to enhancing financial sustainability, the integration of budgets to financial sustainability has a statistically significant impact. This effect is beneficial, and the sort of partial mediation is compatible with the budgets of sustainable financial institutions
Keywords: Government accounting system; financial sustainability